PUBLICATION OF LAWS AND OTHER GENERAL ACTS: HIDDEN POTENTIALS OF E-GOVERNMENT - Zoran R. Jovanovic; Andonović, Stefan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
SummaryThe contemporary democratic values and the rule of law principles imply that all citizens are familiar with the laws and general acts passed by state bodies. Familiarity with the legal norms is the cornerstone of organized society, based on legal foreseeability and the possibility for making plans and decisions. For this purpose, the Constitution of the Republic of Serbia stipulates the obligation of publish laws and other general acts in the public journal (Official Gazette) before their entry into force, so that all interested parties can get familiar with them. However, in the contemporary circumstances of extensive legislative work and a huge number of regulatory acts which are enacted on a daily basis, it seems that citizens and business entities cannot keep up with them all. It poses a risk of harmful consequences for the state, citizens, business entities and other interested stakeholders who fails to comply with the enacted provisions. It gives rise to the following question: is the mere act of publication of laws and general acts in the Official Gazette sufficient in terms of making the interested subjects aware of the new laws and making them comply with the enacted provisions? The authors of the paper believe that it is necessary to go a step further, in the direction of ensuring the active role of the state and, in particular, transforming the mere “publication” of laws into the practice of providing “information” about new regulations. Digitalization and e-government offer ample possibilities for informing the citizens about new regulations. By using different electronic communication tools and developing the potentials of one-stop-shop administrative services, state authorities may ensure a higher degree of compliance with the enacted legal norms. In this paper, the authors aim to contribute to the discussion on these issues by offering their proposals on this matter.
Keywords: digitalization, e-government, one-stop-shop, publication of laws, Official Gazette.